2010
DOI: 10.1111/j.1464-410x.2010.09577.x
|View full text |Cite
|
Sign up to set email alerts
|

Early oncological outcomes for bladder urothelial carcinoma patients treated with robotic‐assisted radical cystectomy

Abstract: Study Type – Therapy (case series) Level of Evidence 4 OBJECTIVE To determine oncological outcomes including early survival rates among unselected bladder urothelial carcinoma (BUC) patients treated with robotic‐assisted radical cystectomy (RRC). PATIENTS AND METHODS Clinicopathologic and survival data were prospectively gathered for 85 consecutive BUC patients treated with RRC. The decision to undergo a robotic rather than open approach was made without regard to tumor volume or surgical candidacy. Kapl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 27 publications
1
27
0
2
Order By: Relevance
“…Kauffman and his team elaborated that these 2 year SCRRC survival data is almost identical to contemporary ORC series [29]. To note, however, surgical margins were positive in five patients [29]. Upon univariate analysis, though, margin positivety was significantly associated with extravesical primary tumor (P<0.01) and LN positivity (P=0.024) [29].…”
Section: Oncological Outcomesmentioning
confidence: 77%
See 3 more Smart Citations
“…Kauffman and his team elaborated that these 2 year SCRRC survival data is almost identical to contemporary ORC series [29]. To note, however, surgical margins were positive in five patients [29]. Upon univariate analysis, though, margin positivety was significantly associated with extravesical primary tumor (P<0.01) and LN positivity (P=0.024) [29].…”
Section: Oncological Outcomesmentioning
confidence: 77%
“…To note, however, surgical margins were positive in five patients [29]. Upon univariate analysis, though, margin positivety was significantly associated with extravesical primary tumor (P<0.01) and LN positivity (P=0.024) [29]. Kauffman et al explained that their positive margin rates met benchmark standards proposed by Herr et al at 6% overall (<10% recommended) and 14% with extravesical disease (<15% recommended) [29,30].…”
Section: Oncological Outcomesmentioning
confidence: 89%
See 2 more Smart Citations
“…Most groups lack long-term follow-up due to the novelty of RARC. Kauffman et al investigated outcomes in 85 RARC patients and reported 2 year recurrence free, cancer specific, and overall survival rates of 74%, 85%, and 79%, respectively [33]. Recent reports from the IRCC revealed overall survival rates of 82% and 71% at 1 and 2 years, respectively.…”
Section: Oncologic Outcomesmentioning
confidence: 99%